Redesign of 13 HP Pakura Boat Engine Exhaust to Reduce Noise Levels - Tumigolung, Stefanny Stevie; Sudrajat, Danu; Susanto, Iwan (Jurnal Kelautan dan Perikanan Terapan (JKPT), 2023)
The hearing level of fishermen in the Lembeh Strait out of 11 fishermen, there are only 2 fishermen whose hearing is still normal. This is likely the effect of a plain exhaust modification and does not use a muffler. The muffler acts as a sound transmission damper when the exhaust gases exit the engine. The objectives of this study are as follows: 1) redesign of the engine exhaust of the pakura boat; 2) analyze the relationship and influence of rotation per minute with laboratory-scale noise levels; and 3) analyze the relationship and influence of rotation per minute with field-scale noise levels. The method used in this research is experimental laboratory and field, comparising one control group and three treatment groups. The results obtained are that there are three types of redesigned exhausts equipped with mufflers. The most effective exhaust for reducing noise levels is exhaust type B, with a range of values between 79-93 dB in laboratory scale and 90-102 dB in field scale.